2013
DOI: 10.2111/rem-d-12-00065.1
|View full text |Cite
|
Sign up to set email alerts
|

Winter Resource Selection by Mule Deer on the Wyoming–Colorado Border Prior to Wind Energy Development

Abstract: Discrete choice modeling is a popular technique in marketing research, transportation, and other areas. It is used to help researchers understand people's stated choice of alternative products and services. We discuss designing a choice experiment, preparing the questionnaire, inputting and processing the data, performing the analysis, and interpreting the results. * Most of the discussion is on designing the choice experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…We view our findings of mule deer avoidance of roads open to motorized vehicle use to be linked to human disturbance, and not the physical features of the road. The strong avoidance of roads open to motorized vehicle use, and associated human disturbance, by ungulates observed in our study and others (Rowland et al 2000, Sawyer et al 2006, Coe et al 2011, Webb et al 2013, Gilbert et al 2017 suggests a substantial portion of what may be suitable habitat may no longer be used (Rogala et al 2011). In a metaanalysis of the effects of flight responses of ungulates to human disturbance, it was found that ungulates, including mule deer, had a strong avoidance and increased movement rates in response to human activity, especially for hunted populations (Stankowich 2008) like our study populations in south-central Oregon.…”
Section: Analysis Area Interceptsupporting
confidence: 74%
See 3 more Smart Citations
“…We view our findings of mule deer avoidance of roads open to motorized vehicle use to be linked to human disturbance, and not the physical features of the road. The strong avoidance of roads open to motorized vehicle use, and associated human disturbance, by ungulates observed in our study and others (Rowland et al 2000, Sawyer et al 2006, Coe et al 2011, Webb et al 2013, Gilbert et al 2017 suggests a substantial portion of what may be suitable habitat may no longer be used (Rogala et al 2011). In a metaanalysis of the effects of flight responses of ungulates to human disturbance, it was found that ungulates, including mule deer, had a strong avoidance and increased movement rates in response to human activity, especially for hunted populations (Stankowich 2008) like our study populations in south-central Oregon.…”
Section: Analysis Area Interceptsupporting
confidence: 74%
“…One of the strongest patterns we observed across all 3 spatio‐temporal analyses was a consistent avoidance of roads open to motorized vehicle use, which has also been documented in Wyoming, Colorado, and southeast Alaska (Sawyer et al , Webb et al , Northrup et al , Gilbert et al ). In contrast, in Idaho, where mule deer shared winter range with elk, mule deer were closer to roads during winter, whereas elk used areas farther from roads (Stewart et al ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Some of these approaches included visual comparison of an RSF map and used points (Mashintonio, Pimm, Harris, van Aarde, & Russell, 2014), generating a contingency table (Mace, Waller, Manley, Ake, & Wittinger, 1999), calculating a correlation between two RSF surfaces built with different data (Brook & McLachlan, 2009), and reporting the percentage of location data in 5 equal sized bins (Webb, Dzialak, Kosciuch, & Winstead, 2013). Multiple studies employed more than one approach to testing predictive accuracy, which is why the methods we describe do not sum to the total number of studies reviewed (101).…”
Section: Resultsmentioning
confidence: 99%